Advising parents when their child has a fever: a phenomenographic analysis of nurses’ perceptions when working at a telephone helpline, at primary care or at a paediatric emergency department in Sweden - Carina Elmqvist; Anders Svensson; Marta Sund-Levander; Emma Westin; Ingrid L Gustafsson (BMJ Open)
Objectives To describe nurses’ perceptions of advising parents when their child has a fever.Design/method Inductive, descriptive study with a qualitative, phenomenographic approach.Participants and setting A purposive sampling was used. To be included, the 24 online interviewed nurses had to have experience advising parents of febrile children between birth and 5 years of age. They were recruited from three different parts of the healthcare system from four regions in the south of Sweden.Results The nurses described advising parents when their child has a fever as four different kinds of balancing acts: balancing between the parents’ story and objective assessment, balancing between listening and teaching, balancing between self-confidence and trust in the expert, and balancing between independence and having someone by one’s side.Conclusions Giving advice to parents when their child has a fever is a process where the nurse needs to listen, assess and give advice based on the situation. This requires a correct assessment that depends on the parents’ story. Creating a trusting relationship is perceived as necessary for parents to assimilate the advice that is provided. What dominates are the nurses’ perceptions of the inner qualities required to achieve a balance in the process, for example, the importance of experience and security in their professional role, while it is also necessary to get support from colleagues.